Trauma-Induced Rupture of Liver Hydatid Cyst: A Rare Cause of Anaphylactic Shock - Khaled, Charif; Kachi, Antoine (The Surgery Journal, 2021)
Hydatid disease is rare; nevertheless, several areas of the world are endemic. Lebanon is one of the endemic countries. This disease requires careful management, as its diagnosis is tough, and its complications are severe and can lead to sudden death. These complications include fistulas, infection, and rupture. Rupture of a hydatid cyst can mimic acute abdomen and show an array of nonspecific symptoms. It could be mistaken for hemorrhagic shock, trauma, or injury to an intra-abdominal organ. The diagnosis of ruptured hydatid cyst should be kept in mind in cattle-raising countries. We report the case of a polytrauma patient who was suspected to have severe intra-abdominal bleeding and hemorrhagic shock, but imaging and laparotomy showed the rupture of a liver hydatid cyst that drove the patient into anaphylactic shock. This article reviews similar cases in the literature and discusses the diagnostic tools, appropriate management, and expected complications.
Keywords: hydatid disease; hydatid cyst; hydatid cyst rupture; anaphylactic shock